2011
DOI: 10.1002/ana.22448
|View full text |Cite
|
Sign up to set email alerts
|

Visinin‐like protein‐1: Diagnostic and prognostic biomarker in Alzheimer disease

Abstract: Objective There is a growing need to identify cerebrospinal fluid (CSF) markers that can detect Alzheimer’s disease (AD) pathology in cognitively normal individuals since it is in this population that disease-modifying therapies may have the greatest chance of success. While AD pathology is estimated to begin ~10–15 years prior to the onset of cognitive decline, substantial neuronal loss is present by the time the earliest signs of cognitive impairment appear. Visinin-like protein −1 (VILIP-1) has demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
165
4
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 139 publications
(185 citation statements)
references
References 42 publications
14
165
4
2
Order By: Relevance
“…AD risk groups within the MCI groups of patients were defined by the levels of five CSF AD biomarkers (Aβ 1-42 , t-tau, p-tau 181 ,p-tau 199 , and ptau 231 ). We tested VILIP-1 effectiveness in early detection of AD in MCI patients, and confirmed previous observations that VILIP-1 is a useful biomarker in early AD diagnosis [12,17,[27][28][29][30]]. Additionally, we tested VILIP-1 potential in differentiating AD from other primary causes of dementia, and its ability in predicting disease progression.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…AD risk groups within the MCI groups of patients were defined by the levels of five CSF AD biomarkers (Aβ 1-42 , t-tau, p-tau 181 ,p-tau 199 , and ptau 231 ). We tested VILIP-1 effectiveness in early detection of AD in MCI patients, and confirmed previous observations that VILIP-1 is a useful biomarker in early AD diagnosis [12,17,[27][28][29][30]]. Additionally, we tested VILIP-1 potential in differentiating AD from other primary causes of dementia, and its ability in predicting disease progression.…”
Section: Discussionsupporting
confidence: 73%
“…Surprisingly, there was no significant difference in VILIP-1 levels between patients with mild and moderate AD. Other authors however reported that VILIP-1 levels and VILIP-1/Aβ 1-42 ratio predict cognitive decline in cognitively healthy individuals and AD patients [27,28]. Both parameters predicted conversion of CDR 0 HC group to CDR 0.5 or higher [27].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The ratio of YKL-40 to Aβ42 predicts cognitive impairment as well as the best CSF biomarkers (Aβ42, t-tau, and p-tau) [83] , suggesting potential as a biomarker for preclinical AD. dementias, and that CSF VILIP-1/Aβ42 predicts cognitive impairment as well as tau/Aβ42 and p-tau181/Aβ42 [84,85] . …”
mentioning
confidence: 97%